Validation of Wavelength-Dispersive X-Ray Fluorescence Technique for Rapid Screening Iron and Zinc Concentration in Rice Seed - Orpong, Piyanuch; Boonsirichai, Kanokporn; Picha, Roppon; Funklin, Ratchai; Kongsri, Supalak; Kukusamude, Chunyapuk; Naksuriyawong, Sasiwimon (Trends in Sciences, 2024)
This study focuses on the validation of a wavelength dispersive X-ray fluorescence (WD-XRF) spectrometer for the rapid determination of iron (Fe) and zinc (Zn) concentrations in certified reference materials (CRMs). Five CRMs were used to establish calibration curves. The results were analyzed in terms of accuracy, precision, repeatability and linearity to assess the performance of the WD-XRF method. Accuracy was evaluated by comparing measured values to certified values, with relative accuracy calculated for each sample. Precision was determined through repeatability, where samples were measured in at least 7 replicates across different days, and relative standard deviation (RSD) was calculated. Linearity was assessed by plotting measured intensities and concentrations against certified concentrations, with the correlation coefficient (R2) values close to 1, indicating a strong linear relationship. Additionally, the WD-XRF method demonstrated high repeatability, with low RSD values across multiple measurements. The study concluded that WD-XRF is a reliable method for the rapid analysis of elemental composition, providing strong accuracy, precision and linearity for Fe and Zn determination in CRMs and can be applied as a valuable method for rapid and non-destructive analysis in various agricultural and food-related applications. HIGHLIGHTS The effectiveness of wavelength dispersive X-ray fluorescence (WD-XRF) method was evaluated to confirm its reliability for determining the elemental composition, specifically iron (Fe) and zinc (Zn), in plant-based certified reference materials (CRMs). Five CRMs were used for calibration and 2 known samples were used as the test samples to determine the analytical performance of WD-XRF. The linearity and correlation with the certified values of WD-XRF results revealed strong correlation with R-square being greater than 0.95 and the recovery percentage of 2 known samples were range from 98.75 - 109.66 for Fe and Zn concentration. WD-XRF spectrometer can be used as a rapid method for determination of Fe and Zn concentrations in rice seeds. GRAPHICAL ABSTRACT